The Product of glnL Is Not Essential for Regulation of Bacterial Nitrogen Assimilation - Backman, Keith C. (1983)
The glnL product is not necessary for the control of expression of glnA and other nitrogen-regulated genes, but it presumably communicates reduntant information on the availability of ammonia from an ammonia-sensitive system consisting of the products of glnB and glnD to the regulatory products of glnF and glnG.